Professional identity and its associated psychosocial factors among physicians from standardized residency training programs in China: a national cross-sectional study - Zeng, Zixuan; Lu, Zhanghong; Zeng, Xiaoping; Gan, Yong; Jiang, Jiahui; Chen, You; Huang, Lei (Frontiers in Medicine, 2024)
Introduction Shortage and high turnover intention rate of physicians are concerning problems in China. Professional identity has been shown as an influential factor for physicians’ turnover intention. Enhancing physicians’ professional identity in their early phase of career, standardized residency training program (SRTP), may help reduce the turnover rate. This study aimed to investigate the current status of professional identity and explore its associated psychosocial factors among Chinese SRTP trainees, hoping to provide evidence in strengthening the available medical human resources in China. Methods The final sample was comprised of 2,267 Chinese SRTP trainees in this cross-sectional survey conducted from 9 March to 20 March in 2023. Descriptive statistics were calculated. Bivariate analyses and hierarchical multiple linear regression were used to analyze potential associated factors of Chinese SRTP trainees’ professional identity. Results The average score of respondents’ professional identity was 47.68 (standard deviation, SD = 8.61). Results from hierarchical multiple linear regression analysis showed that being married (β = 0.066, p < 0.01), having work experience before SRTP (β = 0.036, p < 0.05), being satisfied with annual income (β = 0.062, p < 0.01), psychological distress (β = −0.144, p < 0.001), depersonalization (β = −0.053, p < 0.05), emotional exhaustion (β = −0.380, p < 0.001) and resilience (β = 0.169, p < 0.001) were associated with professional identity (F = 114.301, p < 0.001). All associated factors can explain 41.1% of the variance in professional identity, and individual psychological variables make up a substantial portion (28.6%) of this influence. Discussion Individual psychological variables are strongly associated with professional identity. Helping SRTP trainees reduce psychological distress, alleviate burnout and enhance resilience may be effective ways to promote the formation of their professional identity.